APPLICATION OF CLOUD TECHNOLOGY IN THE STOMATOLOGISTS EDUCATIONAL PROCESS - Oksana A. Zorina; Irina S. Berkutova; Natalia B. Petrukhina (Открытое образование (Москва))
Study the possibility of applying cloud technologies for the control of knowledge and the certification of specialists has been studied in the framework of realization of educational programs of internship and residency training in dental specialties. It was found that the management of the educational process in online mode is possible on the basis of distance education technologies using cloud technology.